Model to aid teaching of electronic apex locator use for endodontics in dental pre-clinical training – a UiTM experience pilot study / Muhamad Asyraf Berhanuddin ... [et al.] - Berhanuddin, Muhamad Asyraf; Mohamad, Nurul Fasiha; Ayoub, Afzan Adilah; Kamaruzaman, Marlena; Baharuddin, Izyan Hazwani; Ismail, Ikmal Hisham (Faculty of Dentistry, Universiti Teknologi MARA, 2021)
Electronic Apex Locators (EAL) has been increasingly used to facilitate working length determination in endodontics. This instrument is becoming more important to be used in addition to radiographs. A steep learning curve has existed between EAL use in the clinical, from the pre-clinical settings. To fabricate a model that will facilitate dental students to use Electronic Apex Locator (EAL) in the dental simulation clinic and to conduct a questionnaire-based survey to investigate Electronic Apex Locator Model (EALM) effectiveness. Construction of model master jaw, EALM, using materials available in the prosthetic laboratory. The model can be mounted on the phantom head which when connected to an EAL will simulate its clinical use. A validated questionnaire was distributed to a group of n=10 pre-clinical students before and after demonstration conducted at the simulation clinic. Results: A prototype EALM was successfully fabricated at Universiti Teknologi MARA Dental Prosthetic Laboratory. with features incorporating conductive-media-chamber, with attached anatomically-correct fabricated model teeth. The teeth were constructed incorporating continuous access cavity, root canal, through to a patent apex. When attached to the jaw model, the electrical circuit was connected allowing EAL to function. Conclusion: EALM can be conveniently constructed at the Dental Prosthetic Laboratory by using materials readily available here. Furthermore, a steep learning curve exist between pre-clinical and clinical studies was bridged by the use this EALM and this allowed familiarity of clinical handling EAL. However, this study was limited by the small number of students exposed to this new method. Further prospective study is required by increasing the sample size to provide more significant results.